Constituintes químicos de Combretum fruticosum ( Loefl.) Stuntz (Combretaceae) - Souto, Augusto Lopes (2011)
The species Combretum fruticosum (Loefl.) Stuntz belongs to the Combretaceae family and is popularly known as pente de macaco or mufumbo , it´s a neotropical plant, which can be found from Mexico until Argentina. This work describes the isolation and structural identification of a few chemical constituents of Combretum fruticosum (Loefl.) Stuntz aerial parts, with the objective of increasing the chemotaxonomic knowledge of the genus Combretum, as well as the family Combretaceae, besides doing biological studies with the isolated substances from this species. The phytochemical study of the Combretum fruticosum (Loefl.) Stuntz aerial parts led to the isolation of the compounds α-amyrin and β-amyrin (CF1), betulinic acid (CF2), α-spinasterol (CF3), spinasterol glycoside acetate (CF4), 132- hydroxy-(132-S)-phaeophytin-a (CF5) and 24-methylene cycloartanyl phydroxycinnamate (CF6). All of them reported for the first time on the genus, except for CF2. These compounds were identified by analysis of data obtained from spectroscopic methods such as infrared and NMR of 1H and 13C, with the aid of two dimensional techniques, besides comparison with literature data. On the biological study of Combretum fruticosum (Loefl.) Stuntz an evaluation of the antimicrobial activity from its crude extract has been made by the essay on agar diffusion against the bacteria and fungi Staphylococcus aureus, Enterococcus faecalis, Klebsiella pneumoniae, Pseudomonas aeruginosa, Escherichia coli, Candida parapsilosis, Candida albicans, Candida krusei and Candida glabrata, which demonstrated antimicrobial activity against the fungus Candida krusei and the bacteria Pseudomonas aeruginosa, Staphylococcus aureus and Enterococcus faecalis. Besides this essay, the evaluation of antitumoral activity in vitro with the substances CF1, CF2, CF3 and CF4 against Sarcoma 180 and K562 cells has been made, which did not show any citotoxic activity on concentrations until 200 μg/mL.